2000
DOI: 10.3310/hta4200
|View full text |Cite
|
Sign up to set email alerts
|

Routine referral for radiography of patients presenting with low back pain: is patients' outcome influenced by GPs' referral for plain radiography?

Abstract: Rink E, Lord J. Routine referral for radiography of patients presenting with low back pain: is patients' outcome influenced by GPs' referral for plain radiography ? Health Technol Assess 2000;4(20).Health Technology Assessment is indexed in Index Medicus/MEDLINE and Excerpta Medica/ EMBASE. Copies of the Executive Summaries are available from the NCCHTA website (see overleaf). NHS R&D HTA ProgrammeT he overall aim of the NHS R&D Health Technology Assessment (HTA) programme is to ensure that high-quality resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 59 publications
(70 reference statements)
0
22
0
2
Order By: Relevance
“…Then, screening the full-text article excluded 17 references, leaving 15 references for inclusion [11,[14][15][16][28][29][30][31][32][33][34][35][36][37][38]. Three RCTs were published twice [15,28,[35][36][37][38] and one trial had three different publications [11,33,34]. Although the DAMASK trial had 6 publications [14,[39][40][41][42][43] only one [14] met the inclusion criteria.…”
Section: Results Of the Search And Description Of Studiesmentioning
confidence: 99%
“…Then, screening the full-text article excluded 17 references, leaving 15 references for inclusion [11,[14][15][16][28][29][30][31][32][33][34][35][36][37][38]. Three RCTs were published twice [15,28,[35][36][37][38] and one trial had three different publications [11,33,34]. Although the DAMASK trial had 6 publications [14,[39][40][41][42][43] only one [14] met the inclusion criteria.…”
Section: Results Of the Search And Description Of Studiesmentioning
confidence: 99%
“…In primary care settings, the most common spine imaging tests for assessing LBP are plain radiography, computed tomography (CT), magnetic resonance imaging (MRI), and bone scanning. Low cost and ready availability make plain radiography the most common of these [8,9]. However, a systematic review of published observational studies found no strong evidence supporting the presence of a causal relationship between radiographic findings and nonspecific LBP [10].…”
Section: Introductionmentioning
confidence: 99%
“…Trials reported in 2000 and 2001 randomizing radiography investigations for low back pain were only able to recruit 23% and 51% of patients approached to enter the randomised arms [15,16]. By assessing patients' willingness to undergo randomisation, potential barriers and facilitators to participation can be identified and used to modify the design of the definitive trial.…”
Section: Introductionmentioning
confidence: 99%